Banking mergers and acquisitions and their impact on creditors' rights: (Comparative analytical study) - Faidhullah, hussain Tofik; Ibrahim Shexa, kazhaw Qadr (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
This research included a definition of concepts related to bank mergers and acquisitions in terms of their definition in jurisprudence and their images and their legal nature. The research also showed the potential effects of mergers and acquisitions on the rights of ordinary creditors and creditors from bondholders. The research reached several conclusions, including that the Iraqi legislature did not regulate the rights of bondholders and their right to form associations, whether in mergers or acquisitions. Among the most important recommendations of the research is to regulate the rights of the creditors of the banks involved in the merger or acquisition with special detailed provisions and their right to object to the merger or acquisitions decision and not leave the matter to the provisions of the general rules